The efectiveness of dry cupping and hot pack on pain relief and reduced functional disability for patients with non-specific low back pain - Azira Iqlima Razali (Tanjong Malim, 2021)
The efectiveness of dry cupping and hot pack on pain relief and reduced functional disability for patients with non-specific low back pain by Azira Iqlima Razali